THE ROLE OF SCHOOLS IN OVERCOMING THE MARGINALIZATION OF THE CHILDREN THROUGH RELIGIOUS EDUCATION IN INDONESIA - Linda Hasim; Henoch Budiyanto; Sutrisno Sutrisno; Christiani Hutabarat (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
Marginalization and prejudice are major challenges in civilizations around the world. As a result, developing measures to foster tolerance among young people is essential in the fight against prejudice. Religious education and awareness initiatives are one approach to achieving this goal. Indonesia schools and colleges, for example, may play an important role in developing tolerance and understanding among young people. Lessons about diversity, inclusivity, and respect for others can be incorporated into teacher curricula. Teaching about the history of prejudice and its impact on various groups, as well as promoting critical thinking and open-mindedness can all be part of this. This research aims to raise awareness, and in addition to religious education, can help develop tolerance and understanding. These religious educational programs against discrimination can be carried out by government agencies, non-governmental organizations, or community organizations. Finally, it is very important to recognize that promoting tolerance and fighting discrimination is a long-term process that requires ongoing effort and commitment. Religious education can help create more inclusive and equitable societies for all by working together to design and implement successful initiatives in Indonesia. it is very important to recognize that promoting tolerance and fighting discrimination is a long-term process that requires ongoing effort and commitment. Religious education can help create more inclusive and equitable societies for all by working together to design and implement successful initiatives. It is very important to recognize that promoting tolerance and fighting discrimination is a long-term process that requires ongoing effort and commitment. Religious education can help create more inclusive and equitable societies for all by working together to design and implement successful initiatives in Indonesia.